INTEGRATION OF SOCIAL CONCEPTS IN THE INTERPRETATION OF THE QURAN: A STUDY OF THE RELATIONSHIP BETWEEN THE SOCIAL AND THE SPIRITUAL - Mhd Syahriel Fahdzlan; M.Hanafi Ramadhan Ginting; Brian Avandi (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2023)
Abstract This study investigates the integration of social and spiritual values in Qur'anic Tafsir, analyzing both classical and contemporary interpretations. Through a qualitative approach utilizing hermeneutical and thematic content analysis, the research examines how key mufassirun, such as al-Tabari, Ibn Kathir, al-Qurtubi, Quraish Shihab, Sayyid Qutb, and Maududi, interpret Qur'anic teachings on justice, poverty, and human relations. The findings reveal that social values such as justice and charity are deeply intertwined with spiritual principles, with both classical and modern Tafsir emphasizing the necessity of integrating personal piety with social responsibility. Contemporary scholars have further developed these concepts to address modern challenges like economic inequality and human rights, demonstrating the enduring relevance of Qur'anic guidance for today’s societal issues. This research contributes to the broader discourse on Islamic ethics and the role of religion in social reform, highlighting the balance between spiritual growth and the pursuit of social justice.